Pengukuran Kinerja dengan Pendekatan Balance Scorecard pada PT. BPR Balerong Bunta - Sri Amelia (Jurnal Ilmiah Raflesia Akuntansi, 2019)
The balance scorecard is a company performance measurement method that combines financial and non-financial measures as a whole that outlines the company's vision and strategy covering four perspectives, namely financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This study aims to measure the performance of PT BPR BalerongBunta based on the Balance Scorecard approach. This type of research is field research using quantitative descriptive methods. The study was conducted at PT BPR BalerongBunta, the data obtained in the form of documents, the results of interviews and the results of distributing questionnaires to 99 customers and 14 employees of PT BPR BalerongBunta. Data analysis techniques used are financial perspective using profitability ratios (ROA), productive asset quality ratios (NPLs), and liquidity ratios (LDR), customer perspectives using customer satisfaction, internal business processes using AETR ratios and for growth and learning perspectives using satisfaction employees, employee productivity and employee retention. The results of this study indicate that the performance of PT BPR BalerongBunta in terms of Financial Perspectives produces good performance. Customer perspective produces good performance. Internal business process perspectives produce good performance. And for the perspective of learning and growth produces good performance.